2005
DOI: 10.1242/dev.01674
|View full text |Cite
|
Sign up to set email alerts
|

A pair of Sox: distinct and overlapping functions of zebrafish sox9 co-orthologs in craniofacial and pectoral fin development

Abstract: Understanding how developmental systems evolve after genome amplification is important for discerning the origins of vertebrate novelties, including neural crest, placodes, cartilage and bone. Sox9 is important for the development of these features, and zebrafish has two co-orthologs of tetrapod SOX9 stemming from an ancient genome duplication event in the lineage of ray-fin fish. We have used a genotype-driven screen to isolate a mutation deleting sox9b function, and investigated its phenotype and genetic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
381
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(413 citation statements)
references
References 131 publications
(193 reference statements)
29
381
3
Order By: Relevance
“…The corresponding orthologs share significantly similar sequences and expression patterns. These findings indicate that the genetic networks controlling bone formation are highly conserved in all vertebrates (Fisher et al, 2003;Flores et al, 2004;Yan et al, 2005;Renn et al, 2006b;Nemoto et al, 2007).…”
Section: Introductionmentioning
confidence: 74%
“…The corresponding orthologs share significantly similar sequences and expression patterns. These findings indicate that the genetic networks controlling bone formation are highly conserved in all vertebrates (Fisher et al, 2003;Flores et al, 2004;Yan et al, 2005;Renn et al, 2006b;Nemoto et al, 2007).…”
Section: Introductionmentioning
confidence: 74%
“…We analyzed expression of foxd3, sox10, sox9b, and snail1b, which label a broad spectrum of ncc subtypes (Yan et al, 2005;Lister et al, 2006). These markers were analyzed at 11-12 hpf (1-3 somite stage) in embryos injected with 150 pg mdkb RNA or 10 ng mdkb MO.…”
Section: Mdkb Regulates Formation Of the Presumptive Neural Crest Domainmentioning
confidence: 99%
“…Extensive comparative genomics studies have corroborated the proposition that gnathostomes have experienced two rounds of genome duplication (2R) (Sidow, '96;Amores et al, '98;Taylor et al, 2003;Vandepoele et al, 2004;Dehal and Boore, 2005). Moreover, another round (3R) genome duplication, the so-called ''fish-specific genome duplication'' (FSGD) took place about 320 mya ago in the ancestral lineage of the teleosts (see e.g., Amores et al, '98;Wittbrodt et al, '98;Gregory and Hebert, '99;Taylor et al, 2003;Hoegg et al, 2004;Vandepoele et al, 2004;Hoegg and Meyer, 2005;Meyer and Van de Peer, 2005;Yan et al, 2005;Crow et al, 2006).…”
mentioning
confidence: 99%
“…Teleosts comprise more than 97% of the approximately 25,000 species of actinopterygians (rayfinned fishes) (Nelson,'94) and are the most species-rich and diverse group of vertebrates. Several authors suggested that the FSGD is at least partially responsible for the species diversity of teleosts (e.g., Amores et al, '98;Wittbrodt et al, '98;Meyer and Van de Peer, 2005;Yan et al, 2005; but see Donoghue and Purnell, 2005).…”
mentioning
confidence: 99%